Rekonstruksi Minat Belajar Peserta Didik Abad 21 Melalui Model Sistem Dinamis - Rini Rahma Safitri; Gita Asyari; Dara Avira; Abdul Fattah Nasution (Pusat Riset dan Inovasi Nasional, 2025)
This study is motivated by the decline in 21st century students' interest in learning caused by various factors, such as conventional learning methods that are not relevant to everyday life and lack of active involvement in the learning process. The research method used is a literature study or Library Research, by collecting data from various relevant literature sources. This study resulted in 3 important themes of findings, namely: 1. Flipped Classroom, 2. Mindfullness and emotional well-being, 3. Peer teaching. The purpose of this study is to contribute to the development of a dynamic system model that can increase the learning interest of 21st century learners.